Global REACH 2018: increased adrenergic restraint of blood flow preserves coupling of oxygen delivery and demand during exercise at high‐altitude. (12th July 2022) - Hansen, Alexander B.; Moralez, Gilbert; Amin, Sachin B.; Hofstätter, Florian; Simpson, Lydia L.; Gasho, Christopher; Tymko, Michael M.; Ainslie, Philip N.; Lawley, Justin S.; Hearon, Christopher M.
Abstract : Abstract: Chronic exposure to hypoxia (high‐altitude, HA; >4000 m) attenuates the vasodilatory response to exercise and is associated with a persistent increase in basal sympathetic nerve activity (SNA). The mechanism(s) responsible for the reduced vasodilatation and exercise hyperaemia at HA remains unknown. We hypothesized that heightened adrenergic signalling restrains skeletal muscle blood flow during handgrip exercise in lowlanders acclimatizing to HA. We tested nine adult males ( n = 9) at sea‐level (SL; 344 m) and following 21–28 days at HA (∼4300 m). Forearm blood flow (FBF; duplex ultrasonography), mean arterial pressure (MAP; brachial artery catheter), forearm vascular conductance (FVC; FBF/MAP), and arterial and venous blood sampling (O2 delivery ( D O 2 D_O_2 ) and uptake ( V ̇ O 2 V_O_2 )) were measured at rest and during graded rhythmic handgrip exercise (5%, 15% and 25% of maximum voluntary isometric contraction; MVC) before and after local α‐ and β‐adrenergic blockade (intra‐arterial phentolamine and propranolol). HA reduced ΔFBF (25% MVC: SL: 138.3 ± 47.6 vs . HA: 113.4 ± 37.1 ml min −1 ; P = 0.022) and Δ V ̇ O 2 V_O_2 (25% MVC: SL: 20.3 ± 7.5 vs . HA: 14.3 ± 6.2 ml min −1 ; P = 0.014) during exercise. Local adrenoreceptor blockade at HA restored FBF during exercise (25% MVC: SLα–β blockade : 164.1 ± 71.7 vs . HAα–β blockade : 185.4 ± 66.6 ml min −1 ; P = 0.947) but resulted in an exaggerated relationship between D O 2 D_O_2 and V ̇ O 2 V_O_2 ( D O 2 D_O_2 / V ̇ O 2 V_O_2 slope: SL: 1.32; HA: slope: 1.86; P = 0.037). These results indicate that tonic adrenergic signalling restrains exercise hyperaemia in lowlanders acclimatizing to HA. The increase in adrenergic restraint is necessary to match oxygen delivery to demand and prevent over perfusion of contracting muscle at HA. Key points: In exercising skeletal muscle, local vasodilatory signalling and sympathetic vasoconstriction integrate to match oxygen delivery to demand and maintain arterial blood pressure. Exposure to chronic hypoxia (altitude, >4000 m) causes a persistent increase in sympathetic nervous system activity that is associated with impaired functional capacity and diminished vasodilatation during exercise. In healthy male lowlanders exposed to chronic hypoxia (21–28 days; ∼4300 m), local adrenoreceptor blockade (combined α‐ and β‐adrenergic blockade) restored skeletal muscle blood flow during handgrip exercise. However, removal of tonic adrenergic restraint at high altitude caused an excessive rise in blood flow and subsequently oxygen delivery for any given metabolic demand. This investigation is the first to identify greater adrenergic restraint of blood flow during acclimatization to high altitude and provides evidence of a functional role for this adaptive response in regulating oxygen delivery and demand. Abstract : Abstract figure legend Exercise hyperaemia is reduced after exposure to high altitude (HA), but oxygen delivery is maintained by increased oxygen carrying capacity of blood. In healthy male lowlanders exposed to chronic hypoxia (21–28 days; ∼4300 m), local adrenoreceptor blockade (combined α‐ and β‐adrenergic blockade) restored skeletal muscle blood flow responses during handgrip exercise. However, removal of tonic adrenergic restraint at high altitude caused an excessive rise in blood flow and oxygen delivery relative to metabolic demand. Therefore, greater adrenergic restraint of blood flow during acclimatization to high altitude is a functional adaptation to that regulates oxygen delivery and demand.